1998
DOI: 10.1038/sj.onc.1201835
|View full text |Cite
|
Sign up to set email alerts
|

Absence of p53-dependent cell cycle regulation in pluripotent mouse cell lines

Abstract: We examined the expression of p53 in three lines of pluripotent embryonal carcinoma (EC) and ES cells. p53 mRNA and protein levels were constitutively high in two lines but absent from one. In the P19 line of EC cells neither p53 protein nor mRNA was detected. The ®rst intron of the p53 gene in these cells had been invaded by a murine leukemia virus and there was extensive hypermethylation of the p53 gene accompanying its inactivation. In all three cell lines, irradiation resulted in arrest of the cells in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Our evidence for p53-independent developmental arrest in borealin À/À p53 À/À embryos is consistent with previous work which describes p53-independent cell cycle arrest and apoptosis in mouse embryonic stem cells (Prost et al, 1998;Aladjem et al, 1998;Schmidt-Kastner et al, 1998). Our work suggests that similar p53-independent mechanisms may exist in embryonic tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Our evidence for p53-independent developmental arrest in borealin À/À p53 À/À embryos is consistent with previous work which describes p53-independent cell cycle arrest and apoptosis in mouse embryonic stem cells (Prost et al, 1998;Aladjem et al, 1998;Schmidt-Kastner et al, 1998). Our work suggests that similar p53-independent mechanisms may exist in embryonic tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to wild-type ES cells (36,37), H2AX ⌬/⌬ ES cells, as well as XRCC4 Ϫ/Ϫ ES cells, arrest at G 2 on exposure to 1,000 rad of IR (Fig. 4, which is published as supporting information on the PNAS web site, www.pnas.org).…”
Section: H2ax-deficient Cells (mentioning
confidence: 99%
“…p53 is known to transactivate p21, which inhibits cyclin D-CDK4/6 complexes to arrest the cells at the G 1 /S border (31). It was reported that embryonal stem cells and embryonal carcinoma cells lack the G 1 /S checkpoint even though p53 is highly activated after X-irradiation (37,40). In a recent study on ␥-irradiated F9 embryonal carcinoma cells, p53 was shown to activate transcription of the p21 gene, but a rapid degradation blocked accumulation of p21 protein, leading to elimination of the G 1 /S checkpoint (29).…”
Section: Vol 22 2002 P53-dependent S-phase Checkpoint In Mouse Zygomentioning
confidence: 99%